Global, regional, and national burden of esophageal cancer: a systematic analysis of the Global Burden of Disease Study 2021 - Weiqiu Jin; Kaichen Huang; Ziyin Ding; Mengwei Zhang; Chongwu Li; Zheng Yuan; Ke Ma; Xiaodan Ye (Biomarker Research)
Abstract Background and objective Esophageal cancer (EC) is the seventh most prevalent cancer globally and the sixth leading cause of cancer-related mortality. This study aimed to provide an updated stratified assessment of rates in EC incidence, mortality, and disability-adjusted life-years (DALYs) from 1990 to 2021 by sex, age, and Socio-demographic Index (SDI) at global, regional, and national levels, as well as to project the future trends of EC both globally and regionally. Methods Data about age-standardized rates (ASRs) of incidence (ASIR), mortality (ASDR), probability of death (ASPoD) and DALYs (ASDALYRs) of EC were obtained from the 2021 Global Burden of Disease (GBD) study. Estimated annual percentage changes (EAPCs) and average annual percentage changes (AAPC) were calculated over certain periods to describe the temporal trends of EC burdens. The analyses were disaggregated by sexes, GBD super-regions and regions, nations/territories, age-groups, and SDI quintiles. A Bayesian age-period-cohort (BAPC) model was constructed to project the global and regional EC ASRs in 2022–2035. Results Despite global reductions in EC ASRs, with ASIR, ASDR, and ASDALYR in 2021 of 6.65 [5.88, 7.45] (95% uncertainty interval), 6.25 [5.53, 7.00], and 148.56 [131.71, 166.82], decreasing by 24.9%, 30.7%, and 36.9% in 1990–2021, respectively, the absolute burden numbers were increased from 1990 to 2021, probably because of population growth and aging. Global newly diagnosed cases, deaths, and DALYs of EC increased to 576,529 [509,492, 645,648], 356,263 [319,363, 390,154], and 12,999,265 [11,522,861, 14,605,268] in 2021, by 62.53%, 51.18%, and 33.28% compared to records in 1990. The geographical pattern of EC was consistent: locations with the highest EC incidence and mortality rates were predominantly located in the Asian Esophageal Cancer Belt and African Esophageal Cancer Corridor, with East Asia, Southern Sub-Saharan Africa, and Eastern Sub-Saharan Africa as the GBD regions with the heaviest EC burdens, and Malawi, Eswatini, Mongolia, Zambia, and Zimbabwe with the most EC ASRs in 2021. However, owing to the population size, China, India, the United States, Japan, and Brazil had the heaviest absolute EC burdens. More pronounced alleviations of ASRs were observed in locations with high SDI levels, indicated by their lower AAPC values compared to those of low-SDI locations, while Sub-Saharan Africa regions had increasing EC ASRs, especially in Chad (114.76% in ASDR, for example), Sao Tome and Principe (97.93%), Togo (92.53%), Northern Mariana Islands (84.32%), Liberia (82.33%), etc. Smoking remained the leading contributor to EC ASDALYR globally and across most GBD super-regions in 2021. The EC burden is significantly heavier for males, with incidence and mortality in males in 2021 being 2.89 and 2.88 times higher, respectively, than in females. Across all age groups, EC posed an increasingly significant threat to men aged > 75 years. From 2022 to 2035, the ASR projections show only modest decrease in both global and regional EC burdens, and the absolute burden numbers are expected to increase globally and in nearly all GBD super-regions. Conclusion EC burden remains significant, with disparities across sexes, age groups, and regions. Region-specific and age-targeted measures are crucial to addressing these inequalities, especially in light of increasing EC burdens in older men and in African regions. Efforts should be taken in finding more solid attributions to risk factors for EC burdens and to better identify high-risk populations to inform targeted prevention and screening, and ultimately reduce the EC burden in an efficient and cost-effective way. Graphical Abstract